Case Report: Gait Deterioration in a Patient with EAST (Epilepsy, Ataxia, Sensorineural Deafness, Tubulopathy) Syndrome - Majerník, Gökçe Hatipoğlu; Martin, J. Peter (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Epilepsy, Ataxia, Sensorineural deafness, Tubulopathy (EAST) syndrome or seizures, sensorineural deafness, ataxia, mental retardation (SeSAME) is a very rare, autosomal recessive disorder resulting from homozygous or compound heterozygous loss-of-function variations in the KCNJ10 gene, affecting <1:1.000.000 individuals. Ambulation problems, such as ambulation delays and ataxia, are common in this syndrome. The disorder can remain undiagnosed in adults due to its rarity. Here, we describe the case of a patient with genetically proven EAST syndrome at the age of 18. The patient experienced a dramatic deterioration in his walking ability 7 years after the diagnosis when he was 25 years old. However, the main reason for gait deterioration was cervical spinal cord compression by cervical disc prolapse which was determined through magnetic resonance imaging during further examinations. Cervical myelopathy caused increased spasticity and gait deterioration in this patient. He underwent single-level anterior cervical decompression and fusion without any complication and improved postoperatively. Although worsening neurological findings in patients with EAST syndrome have been reported, in-depth clinical, radiological, and laboratory examinations can clarify the increasing deterioration in motor functions. Concomitant pathologies can occur, which should be kept in mind for better diagnosis and treatment, especially for patients with EAST syndrome.